Artikel Laporan Studi Kelayakan Bisnis “Warkop Kopi Kong” Dikota Palangka-Raya,Kalimantan Tengah - Rahmah Rahmah; Rizal Pramudya; Wa'uqi Febriyan; Hendry Wahyu Hariansano (Universitas Maritim AMNI Semarang, 2024)
This feasibility study report aims to analyze the potential and feasibility of the Warkop Kopi Kong business in Palangka Raya City. This research was conducted using qualitative and quantitative descriptive methods. The data used includes primary and secondary data. Primary data is obtained through surveys of potential consumers and analysis of the business environment, while secondary data is obtained from various sources such as financial reports, demographic data and market trends. The analysis carried out includes market, technical, management and financial aspects. Market analysis includes demand analysis, determining market targets, and competitive analysis. Technical analysis includes site planning, interior design, equipment, and layout. Management analysis includes organizational structure, human resources, and control systems. Financial analysis includes projections of income, costs, and financial feasibility analysis such as Net Present Value (NPV) and Internal Rate of Return (IRR). The analysis results show that the Warkop Kopi Kong business has good potential to develop in Palangka Raya City. This is supported by increasing public interest in coffee, stable economic growth, and the lack of intense competition in the targeted market segment. However, there are several challenges that need to be overcome, such as fluctuations in raw material prices, changes in consumer trends, and increasingly fierce competition in the future. Based on the results of the analysis, it can be concluded that the Warkop Kopi Kong business is feasible to run. However, several efforts need to be made to increase competitiveness and business sustainability, such as developing new products, improving service quality, and optimizing the use of social media for promotions.